RANCANG BANGUN APLIKASI POINT OF SALE & PENJUALAN ONLINE BERBASIS ANDROID PADA TOKO EMAS - Muhammad Alvin Nugraha Sujana (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The primary issue at Toko Emas Rahmat Baru is that operational management relies heavily on manual processes. This condition frequently leads to errors in stock and price recording, the risk of data loss, and limited market reach due to the absence of an online sales channel. This study aims to develop "RahmatMas," an integrated Android-based Point of Sale (POS) and online sales application. A key feature of this system is the implementation of a hybrid (offline-first) architecture, ensuring that transaction recording remains smooth and secure even under unstable internet connectivity. The system development employs the Agile Scrum methodology, characterized by an iterative and incremental approach, enabling rapid adaptation to user feedback. System reliability validation was conducted through System Testing, verified directly using Logcat in Android Studio. Based on testing 20 functional scenarios, each undergoing 5 iterations, the system demonstrated high stability with a 100% success rate and no errors. These results are reinforced by User Acceptance Testing (UAT) across 12 usage scenarios, confirming that the application is well-received by the shop owner and deemed suitable for operational management, including transaction recording, stock management, and sales recapitulation.